Pengaruh Perubahan Book to Market Value, Nilai Tukar, dan Ukuran Perusahaan terhadap Perubahan Return Saham - Yuyetta, Etna Nur Afri (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2010)
Capital market theory is concerned with the equilibrium relationship between risk and expectedreturn on risky assets (Drew, et al (2003). This study aims to investigate the effects of bookto-market value, exchange rate and firm’s size changes on the stock returns. The use of Engle-Granger’s Error Correction Model completed with Cointegration Test, allow this study to testthe short term as well as the long term relationship between variables. The evidence show thatbook-to-market value and exchange rate changes do predict the stock return changes, but not forthe firm’s size. The interpretations and the implications are discussed.